Poly(piperazinyl phosphamide): a novel highly-efficient charring agent for an EVA/APP intumescent flame retardant system. Issue 36 (23rd March 2016) - Dong, Liang-Ping; Deng, Cong; Li, Rui-Min; Cao, Zhi-Jie; Lin, Ling; Chen, Li; Wang, Yu-Zhong
Abstract : Poly(piperazinyl phosphamide) is a kind of novel charring agent, showing highly-efficient charring capacity and good interaction with another flame-retardant component APP in flame retarding EVA. Abstract : Traditional charring agents have two obvious defects, which are low charring efficiency and bad interaction with the other flame-retardant components, leading to the unsatisfying efficiency of an intumescent flame retardant. To overcome the aforementioned disadvantages, a novel phosphorus and nitrogen compound, named poly(piperazinyl phosphamide) (PPPA), was synthesized through a one-step reaction. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) etc., confirmed that PPPA was prepared successfully. Thermogravimetric analysis (TGA) revealed that the char residues of PPPA at 600 °C under N2 and air were 45.3 wt% and 51.6 wt%, respectively. Combustibility tests including oxygen index (OI), vertical burning test (UL-94) and cone calorimeter test (CC) further proved that the PPPA was a highly efficient charring agent from the viewpoint of its application. The OI value of the ethylene-vinyl acetate copolymer (EVA)/ammonium polyphosphate (APP)/PPPA composite reached 30.5%, and it passed the V-0 rating in the presence of only 5.5 wt% PPPA. The Py-GC/MS, FTIR and XPS tests demonstrated that abundant aromatic structures resulting from the decomposition of the PPPA, mainly consisting of CC, CN, P–N and PO etc., facilitated the formation of a stable char layer. Moreover, APP could delay the fracture of the C–N bond in PPPA and catalyze the generation of the benzene ring, further enriching the char residue. So, both the highly-efficient charring capacity of PPPA itself and the synergetic effect resulting from APP and PPPA led to the excellent flame retardation of the EVA composite.